Treatment-refractory vulvodynia from nutcracker syndrome: A case report - Paulina C. Altshuler; Brandon T. Garland; Michael E. Jorgensen; Nel E. Gerig (Elsevier, 2018)
Background: Pelvic venous disorders are often undiagnosed due to the symptom variability and similarity to other disease presentations. 'Pelvic congestion syndrome' is a term often used as a diagnosis of exclusion, since there is currently no standardized diagnostic approach for pelvic venous disorders, which further delays treatment. Case: A 25-year-old woman with treatment-refractory vulvodynia presented with symptoms that included left-sided vaginal wall pain, pruritis, dysmenorrhea, dyspareunia, muscle tension, and a chronic vaginal ulceration. Abnormal pelvic varices were discovered, and she was referred to vascular surgery for treatment of nutcracker syndrome causing ovarian vein reflux and abnormal engorgement of pelvic varices. Conclusion: Patients presenting with signs of pelvic venous insufficiency such as vaginal pruritis, irritation, pain, recurrent vaginitis, or chronic ulcerations should be examined for pelvic venous disorders. Keywords: Chronic pelvic pain, Pelvic congestion syndrome, Pelvic venous disorder, Nutcracker syndrome, Venous stasis, Vulvodynia